2018
DOI: 10.1007/978-3-319-65415-7
|View full text |Cite|
|
Sign up to set email alerts
|

Vital Forces, Teleology and Organization

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“… 14 I agree with Gambarotto (2018) that, contrary to common wisdom, the true vindicator of the Aristotelian concept is not Kant, but Hegel. See also Michelini 2008: 85.…”
Section: Notesmentioning
confidence: 67%
“… 14 I agree with Gambarotto (2018) that, contrary to common wisdom, the true vindicator of the Aristotelian concept is not Kant, but Hegel. See also Michelini 2008: 85.…”
Section: Notesmentioning
confidence: 67%
“…44–45) has suggested that Treviranus paid specific attention to the dynamics of nature and in this way helped pave the way for a more transformist and historical conception of nature. According to Andrea Gambarotto, Treviranus’s work is mostly synthetic, because it brings together various strands of earlier work ( 2018 , p. 93) and follows Schelling in many ways, but goes beyond the latter in presenting the deduction of the “ideal series” of organisms as a “real” and therefore historical sequence of organic forms (Gambarotto 2018 , p. 113). Thus, like de Jager, Gambarotto considers the historicization of nature and of life to be the aspect of Treviranus’s thought that contributed to the emergence of biology.…”
Section: The Axiomatic Methods In Treviranus’s Biologiementioning
confidence: 99%
“…Steigerwald notes that “[i]n the lengthy introduction in the first volume [of his Biologie ], Treviranus laid claim to scientific study of living organisms, modeled after philosophical conceptions of science as a system of knowledge … and founded on certain principles” (Steigerwald 2014 , p. 106). Gambarotto points out that, for Treviranus, “[t]rue science must be based on fundamental principles and deduce all its propositions from them” and that this demand reveals Kant’s and Schelling’s influence (Gambarotto 2018 , p. 94). However, apart from these brief and general remarks, these authors do not discuss this aspect of Treviranus’s work in more detail and focus instead on its more historicist and naturalist strands.…”
Section: The Axiomatic Methods In Treviranus’s Biologiementioning
confidence: 99%
See 1 more Smart Citation
“…Another element possibly missing in the book is context: recent years have seen increasing scholarly interest devoted to the numerous views on nature, life and organism emerging around and mediating the link between Kant and Hegel—such as the work of Schelling, Oken, Eschenmayer or Romantic Naturphilosophie (Richards 2002, and the materials now collected in Zammito 2018, Gambarotto 2018). Khurana does not seem to consider the relevance of practically any of these interlocutors.…”
mentioning
confidence: 99%